2019
DOI: 10.1038/s41467-019-11294-7
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable soft body trajectories using unidirectionally stretchable composite laminae

Abstract: Compliant, continuum structures allow living creatures to perform complex tasks inaccessible to artificial rigid systems. Although advancements in hyper-elastic materials have spurred the development of synthetic soft structures (i.e., artificial muscles), these structures have yet to match the precise control and diversity of motions witnessed in living creatures. Cephalopods tentacles, for example, can undergo multiple trajectories using muscular hydrostat, a structure consisting of aggregated laminae of uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 38 publications
0
59
0
Order By: Relevance
“…With the arrangement of stiff fiber, this actuator can achieve bending, elongation and other movements. Similarly, Kim group reported a lamina composed of not stretchable fiber, super-elastic matrix and an adhesive backing [16]. This lamina also named Stretchable Adhesive Uni-Directional prepreg (STAUD-prepreg) (Figure 1b).…”
Section: Structurementioning
confidence: 88%
“…With the arrangement of stiff fiber, this actuator can achieve bending, elongation and other movements. Similarly, Kim group reported a lamina composed of not stretchable fiber, super-elastic matrix and an adhesive backing [16]. This lamina also named Stretchable Adhesive Uni-Directional prepreg (STAUD-prepreg) (Figure 1b).…”
Section: Structurementioning
confidence: 88%
“…The primary drawback of this type of approach is that when other unplanned deformation modes are introduced, such as buckling, or a change of material properties through damage or natural material aging, the models accumulate error. Additionally, it is unclear how to generalize these advances to reconfigurable soft robots (77) or robots that have more complex morphologies. For example, recent simulations suggest that there are a wide range of soft robot morphologies that could produce useful locomotion, including quadrupedal shapes and various oddly-shaped blobs (78).…”
Section: Shape Sensingmentioning
confidence: 99%
“…Kim et al reported a reprogrammable pneumatic soft robot based on the self-adhesive fiberconstrained unidirectional prepreg (Figure 7c). [135] The motion of the pneumatic soft robot was governed by the prepreg, which can be easily detached and reattached to another one to reconfigure inflation trajectories. Multiple prepregs were stacked up to achieve combined movements.…”
Section: Magnetic and Pneumatic Actuationsmentioning
confidence: 99%
“…Reproduced under the terms of the CC-BY Creative Commons Attribution 4.0 International License (https:// creativecommons.org/licenses/by/4.0/). [135] Copyright 2019, The Authors, published by Springer Nature.…”
Section: Fiber-actuator-based Soft Grippersmentioning
confidence: 99%